Case Report: In Situ Vaccination by Autologous CD16+ Dendritic Cells and Anti-PD-L 1 Antibody Synergized With Radiotherapy To Boost T Cells-Mediated Antitumor Efficacy In A Psoriatic Patient With Cutaneous Squamous Cell Carcinoma - Huang, Jun-Wei; Kuo, Chun-Lin; Wang, Li-Tzu; Ma, Kevin Sheng-Kai; Huang, Wen-Yen; Liu, Feng-Cheng; Yang, Kuender D.; Yang, Bing-Heng (Frontiers in Immunology, 2021)
The combination of radiotherapy and immunotherapy improves the survival rate of patients with malignancies developed through escape from T-cell-mediated immune surveillance. Immune checkpoint inhibitors, such as anti-programmed cell death protein-ligand 1 (anti-PD-L1) antibody, are used to rescue exhausted T cells. Simultaneously, dendritic cells (DCs) which are antigen-presenting cells that can initiate T-cell activation, are used to induce a tumor-specific immune response. However, the synergistic antitumor efficacy of the aforementioned combinational immunotherapy with intratumoral injection of low-dose DCs has not been reported, and the underlying therapeutic mechanism requires further investigation. Herein, we present the special case of a psoriatic patient with cutaneous squamous cell carcinoma (cSCC) in the right inguinal region, these two diseases characterized by opposing contradiction, further complicating treatments and side-effect management efforts. To treat the intractable SCC without exaggerating psoriasis, we developed the triple-regimen therapy (TRT) with the intratumoral injection of low-dose autologous DCs and anti-PD-L1 combined with radiotherapy. The injected DCs were obtained simply through leukapheresis without prior G-CSF administration for mobilization nor tumor-antigen loading for expansion. The patient received three radiation doses (24, 18, and 18 Gy) combined with three intratumoral injections of anti-PD-L1 antibody (40, 60, and 120 mg) plus autologous DCs (80% of the DC subpopulation being CD16+ myeloid DC with approximate amounts of 7.3 × 104, 2.5 × 106, and 1.7 × 107) within 10 weeks. The efficacy of the TRT was encouraging in shrinking tumor mass with remarkable SUVmax reduction (approximately 42%) on FDG PET-Scan despite relatively low-dose DCs were available. The low-dose intratumoral immunotherapy induced mild cutaneous side effects as expected. The transcriptomes were compared between pre-TRT and post-TRT biopsies to analyze underlying mechanical pathways of the TRT protocol. Over 10 highly significantly enriched T-cell-related pathways (P <0.0001) were identified in post-TRT biopsies. In addition, the activation of both innate and adaptive immunity was significantly enriched in post-TRT peripheral blood samples. We develop the easily accessible TRT which produces both local anti-tumor T-cell responses and systemic antitumor immunity for treating cSCC patients, especially for those with autoimmune disease.